Analisis Faktor Risiko Penyakit Distemper pada Anjing di Denpasar - Krisna Erawan, I Gusti Made; Suartha, I Nyoman; Sapta Budiari, Emy; Mustikawati, Diana; Batan, I Wayan (Jurnal Veteriner; Vol 10 No 3 (2009), 2009)
A study was conducted to identify the risk factors of canine distemper in Denpasar, Bali. Risk factorsfor canine distemper were characterized using hospital records of private veterinary practitioners. Thisstudy showed that there was no difference in the susceptibility to canine distemper virus infection betweenmales and females. The occurrence of canine distemper disease is not significantly affected by the season.The risk of canine distemper disease for young dogs, between 0 and 1 year was 4.95-fold increase ascompared the risk of disease for dogs that were older than 1 year (Oods-Ratio: 4.95). Incomplete vaccinationwas associated with a 3.77-fold increase in the risk of canine distemper (Oods-Ratio: 3.77).
Keywords: canine distemper, risk factors, Oods-Ratio